Pregnancy exacerbates neutrophil responses in murine lungs and alters gut microbiota composition after cigarette smoke exposure - Dehghani, Ali; Wang, Lei; Garssen, Johan; Styla, Eirini; Leusink-Muis, Thea; Ark, Ingrid van; Folkerts, Gert; van Bergenhenegouwen, Jeroen; Braber, Saskia (Frontiers in Immunology, 2025)
IntroductionAir pollution, particularly environmental tobacco smoke, poses significant health risks, especially to pregnant women and their infants. This study explores the difference in response to cigarette smoke (CS) exposure between pregnant and non-pregnant mice by examining lung transcriptomic profiles, neutrophil numbers, key mediators of neutrophil chemotaxis, and gut microbiota composition. MethodsPregnant and non-pregnant mice were exposed to either air or CS. Bronchoalveolar lavage fluid (BALF) was analyzed for inflammatory cells and mediators. RNA sequencing was conducted on lung tissue to identify transcriptomic alterations. Gut microbiota composition and short-chain fatty acid (SCFA) levels were assessed to explore the interactions within the gut-lung axis. ResultsCS exposure resulted in a significant increase in inflammatory cells in the BALF, notably neutrophils, with pregnant dams showing a more substantial increase compared to non-pregnant mice. Transcriptomic analysis revealed neutrophil chemotaxis as the most enriched pathway in CS-exposed pregnant dams. Key genes associated with neutrophil-mediated inflammation, such as CXCL1, S100A8, and S100A9, were significantly upregulated. Gut microbiota analysis showed altered composition and reduced alpha and beta diversity in CS-exposed pregnant dams compared with air-exposed pregnant dams, along with compositional differences between CS-exposed pregnant and non-pregnant mice. CS exposure also resulted in a decrease in cecal SCFA levels in pregnant dams. DiscussionIn conclusion, pregnancy as well as CS exposure induce differences in lung transcriptomic responses which might drive exacerbated lung inflammatory responses measured as neutrophil influx and activity. Microbiota functional and compositional states are also affected by both pregnancy and CS exposure, possibly indicating a gut-lung bidirectional effect.